Effect of margins of excision on recurrence after local excision of ductal carcinoma in situ of the breast. Issue 8 (1st August 2002) - Douglas-Jones, A G; Logan, J; Morgan, J M; Johnson, R; Williams, R
Abstract : Aims: To determine important factors influencing recurrence after local excision of duct carcinoma in situ (DCIS) of the breast. Materials and methods: The extent (size) in millimetres, classification (by cytonuclear grade (NHSBSP system), by extent of necrosis, and by the Van Nuys system), and excision margins of 115 cases of screen detected DCIS treated by local excision were measured. A prognostic index was calculated by the addition of the Van Nuys classification (low grade, 1; moderate grade, 2; high grade, 3), margin score (≥ 10 mm, 1; 1–9 mm, 2; < 1 mm, 3), and size score (≤ 15 mm, 1; 16–40 mm, 2; and ≥ 41 mm, 3), giving a total score of 3–9. Results: Classification using cytonuclear grade, extent of necrosis, or the Van Nuys system did not correlate significantly with recurrence. The excision margin (in millimetres) was associated with recurrence (p = 0.027) and if excision margin status was simplified using the scoring system (≥ 10 mm, 1; 1–9 mm, 2; < 1 mm, 3), the margin score was significantly associated with recurrence (p = 0.03). A prognostic index based on the Van Nuys score, margin status, and size was significantly associated with recurrence (p = 0.003). Conclusion: The results support the hypothesis that the margin of excision is the most important factor predicting the recurrence of DCIS after local excision.